Homotopy Perturbation Approach to the Solution of Non-linear Burger's Equation - Snehlata Rathore; Gajendra K. Saraswat (International Journal of Mathematics And its Applications, 2018)
The aim of this paper is to build another effective intermittent connection to explain nonlinear Burgers' equation. The homotopy perturbation technique is utilized to explain this equation. Burger's equation is a popular reaction diffusion equation in the biomathematics on the grounds that Burgers equations emerge in numerous applications, it is worth trying new solution methods. In this method, the solution is considered as an infinite series expansion where it converges rapidly to the exact solution. Numerical experimentation demonstrates the precision of a minimum error of order third for different space steps and coefficient of kinematic viscosity. The technique is viewed as high in accuracy. All calculations has been completed utilizing MATLAB.